The cortical actin network regulates avidity-dependent binding of hyaluronan by the Lymphatic Vessel Endothelial receptor LYVE-1 - Stanly, TA; Fritzsche, M; Banerji, S; Shrestha, D; Schneider, F; Eggeling, C; Jackson, DG (American Society for Biochemistry and Molecular Biology, 2020)
Lymphatic vessel endothelial hyaluronan receptor 1 (LYVE-1) mediates the docking and entry of dendritic cells to lymphatic vessels through selective adhesion to its ligand hyaluronan in the leucocyte surface glycocalyx. To bind hyaluronan efficiently, LYVE-1 must undergo surface clustering, a process that is induced efficiently by the large crosslinked assemblages of glycosaminoglycan present within leucocyte pericellular matrices, but is induced poorly by the shorter polymer alone. These properties suggested that LYVE-1 may have limited mobility in the endothelial plasma membrane, but no biophysical investigation of these parameters has been carried out to date. Here, using super-resolution fluorescence microscopy and spectroscopy combined with biochemical analyses of the receptor in primary lymphatic endothelial cells, we provide first evidence that LYVE-1 dynamics are indeed restricted by the submembranous actin network. We show that actin disruption not only increases LYVE-1 lateral diffusion but also enhances hyaluronan binding activity. However, unlike the related leucocyte HA receptor CD44 which uses ERM and ankyrin motifs within its cytoplasmic tail to bind actin, LYVE-1 displays little if any direct interaction with actin as determined by co-immunoprecipitation. Instead, as shown by super-resolution stimulated emission depletion (STED) microscopy in combination with fluorescence correlation spectroscopy, LYVE-1 diffusion is restricted by transient entrapment within submembranous actin corrals. These results point to an actin-mediated constraint on LYVE-1 clustering in lymphatic endothelium that tunes the receptor for selective engagement with hyaluronan assemblages in the glycocalyx that are large enough to cross-bridge the corral-bound LYVE-1 molecules and thereby facilitate leucocyte adhesion and transmigration.